Highly Elastic and Water Stable Zein Microfibers as a Potential Drug Delivery System for Wound Healing - Alma Akhmetova; Georg-Marten Lanno; Karin Kogermann; Martin Malmsten; Thomas Rades; Andrea Heinz (MDPI AG, 2020)
The development of biomaterials for wound healing applications requires providing a number of properties, such as antimicrobial action, facilitation of cell proliferation, biocompatibility and biodegradability. The aim of the present study was to investigate morphological and mechanical properties of zein-based microfibers, ultimately aimed at creating an environment suitable for wound healing. This was achieved through co-axial electrospinning of core-shell microfibers, with zein protein in the core and polyethylene oxide (PEO) in the shell. Small amounts of PEO or stearic acid were additionally incorporated into the fiber core to modify the morphology and mechanical properties of zein fibers. The presence of PEO in the core was found to be essential for the formation of tubular fibers, whereas PEO in the shell enhanced the stability of the microfibers in water and ensured high elasticity of the microfiber mats. Tetracycline hydrochloride was present in an amorphous form within the fibers, and displayed a burst release as a result of pore-formation in the fibers. The developed systems exhibited antimicrobial activity against Staphylococcus aureus and Escherichia coli, and showed no cytotoxic effect on fibroblasts. Biocompatibility, antimicrobial activity and favorable morphological and mechanical properties make the developed zein-based microfibers a potential biomaterial for wound healing purposes.